Pharmacokinetics profiles of polyphyllin II and polyphyllin VII in rats by liquid chromatography with tandem mass spectrometry. (17th February 2021) - Wang, Genbei; Hao, Ruijia; Luo, Chen; Wang, Yu; Man, Shuli; Gao, Wenyuan
Abstract: Polyphyllin II (PII) and polyphyllin VII (PVII) are the main active ingredients in Paris Polyphylla with an excellent antitumor effect in vitro and in vivo . In this study, a rapid and precise LC–MS/MS method was developed and validated for the separation and simultaneous determination of PII and PVII in rat plasma, tissues, feces and urine using ginsenoside Rg3 as the internal standard. Positive linearity ranged from 1 to 1, 000 ng/ml in samples. At the same time, intra‐ and inter‐day precisions were in range of 1.8–12.0%. The accuracy ranged from 95.9 to 100.8%. Mean extraction recoveries of PII and PVII ranged from 86.6 to 96.4%. The analytical method has been successfully applied to the pharmacokinetic studies of PII and PVII in rats after their i.v. administration. After entering systemic circulation, PII and PVII were rapidly distributed in organs, mainly including liver, lung and spleen. Their elimination rate was slow. All of these data provided a theoretical basis for the application of PII and PVII in the treatment of liver‐ and lung‐related diseases.